“I just think it is the way of the future”: Teachers' use of ChatGPT to develop motivationally-supportive math lessons - Teomara Rutherford; Andrew Rodrigues; Santiago Duque-Baird; Sotheara Veng; Rosa Mykyta-Chomsky; Yiqin Cao; Kristin Chisholm; Ekaterina Bergwall (Computers and Education: Artificial Intelligence)
ChatGPT has quickly infiltrated the educational landscape and teachers are engaging with this tool to support their teaching activities, including lesson development. In this study, eight elementary school teachers are guided in the development of motivationally-supportive mathematics lessons using ChatGPT as a tool to support student positive mathematics emotions, motivation, and engagement as theorized within Control Value Theory (CVT). Results reveal that teachers found ChatGPT useful for this purpose and that the lessons implemented demonstrated some success in fostering motivationally-supportive math activities. Compared to non-ChatGPT lessons, in lessons developed with ChatGPT, the same teachers used more utility value messages, more non-standard examples, and more specific feedback while engaging in less lesson-irrelevant chit-chat. Within these lessons, students also reported feeling less bored and provided fewer negatively-valenced comments compared to non-ChatGPT lessons. The results have implications for the use of ChatGPT as a lesson development tool and demonstrate the success of a CVT-framed intervention.